THE PRICE OF INNOVATION: DETERMINING COST FACTORS IN PREFAB HOUSING - Wei, Liang Jun; Ming, Wang Xiao (Ayden Journal of Management and Social Sciences, 2024)
The rapid pace of urbanization and population growth has necessitated innovative solutions to urban housing challenges, leading to the proliferation of high-rise residential construction. Prefabricated building techniques have emerged as a fast, efficient, and sustainable approach to address these demands. In recent years, prefabricated high-rise residential buildings have gained prominence for their ability to enhance construction quality, shorten project timelines, and minimize resource consumption. However, despite their advantages, prefabricated homes encounter significant cost-related challenges. This paper underscores the importance of conducting a comprehensive evaluation and analysis of the cost factors associated with prefabricated housing to enhance its economic viability and sustainability. By systematically examining the various cost elements involved in prefabricated construction, stakeholders can identify opportunities for cost optimization and efficiency improvement. Such evaluations are essential for informing decision-making processes and guiding policy interventions aimed at promoting the widespread adoption of prefabricated building methods. Drawing upon insights from contemporary literature and empirical studies, this paper elucidates the key cost factors influencing the economic performance of prefabricated housing projects. It explores factors such as material costs, labor expenses, transportation logistics, regulatory compliance, and project management overheads, among others. Through a comprehensive analysis of these cost drivers, stakeholders can develop strategies to mitigate cost escalations and enhance the overall affordability and feasibility of prefabricated housing solutions